Influence of combustion conditions and sample characteristics on Particulate Matter emissions formation from Refused Derived Fuel - Sramka Michal; Nosek Radovan; Holubčík Michal; Kapjor Andrej; Kantová Nikola Čajová; Martauz Pavel; Sochr Jozef (E3S Web of Conferences)
Particulate matter (PM) from solid alternative fuel combustion poses environmental and health concerns. This research investigates atmospheric composition, sample fractions, and sample chemistry effects on PM. TSI Scanning Mobility Particle Sizer and Aerodynamic Particle Sizer quantified PM emissions during Refused Derived Fuel combustion. Nine samples were tested in the thermogravimetric analyzer for different fuel fractions and atmospheres: Air, 100% N2, and 100% O2. Results revealed complex links between concentrations of emissions and PM size distribution varied with atmospheres. The results show PM concentration reduction during combustion of smaller sample fractions. For fractions ≤0.25 mm, PM was 53% less than for 1-0.5 mm. An oxygen-only atmosphere reduced PM by 70% compared to oxygen-free.